Candida albicans and Early Childhood Caries - Menon, Leena U.; Scoffield, Jessica A.; Jackson, Janice G.; Zhang, Ping (Frontiers in Dental Medicine, 2022)
Early childhood caries (ECC) is a highly prevalent and costly chronic oral infectious disease in preschool children. Candida albicans has been frequently detected in children and has demonstrated cariogenic traits. However, since ECC is a multifactorial infectious disease with many predisposing non-microbial factors, it remains to be elucidated whether the presence and accumulation of C. albicans in ECC is merely a consequence of the adaptation of C. albicans to a cariogenic oral environment, or it plays an active role in the initiation and progression of dental caries. This review aims to summarize the current knowledge on C. albicans and the risk of ECC, with a focus on its synergistic relationship with the cariogenic pathogen Streptococcus mutans. We also highlight recent advances in the development of approaches to disrupt C. albicans-S. mutans cross-kingdom biofilms in ECC prevention and treatment. Longitudinal clinical studies, including interventional clinical trials targeting C. albicans, are necessary to ascertain if C. albicans indeed contributes in a significant manner to the initiation and progression of ECC. In addition, further work is needed to understand the influence of other bacteria and fungi of oral microbiota on C. albicans-S. mutans interactions in ECC.